HLA-DQ2.5 genes associated with celiac disease risk are preferentially expressed with respect to non-predisposing HLA genes: Implication for anti-gluten T cell response. (June 2016) - Pisapia, Laura; Camarca, Alessandra; Picascia, Stefania; Bassi, Virginia; Barba, Pasquale; Del Pozzo, Giovanna; Gianfrani, Carmen
Abstract: HLA genes represent the main risk factor in autoimmune disorders. In celiac disease (CD), the great majority of patients carry the HLA DQA1*05 and DQB1*02 alleles, both of which encode the DQ2.5 molecule. The formation of complexes between DQ2.5 and gluten peptides on antigen-presenting cells (APCs) is necessary to activate pathogenic CD4 + T lymphocytes. It is widely accepted that the DQ2.5 genes establish the different intensities of anti-gluten immunity, depending whether they are in a homozygous or a heterozygous configuration. Here, we demonstrated that HLA DQA1*05 and DQB1*02 gene expression is much higher than expression of non-CD-associated genes. This influences the protein levels and causes a comparable cell surface exposure of DQ2.5 heterodimers between DQ2.5 homozygous and heterozygous celiac patients. As a consequence, the magnitude of the anti-gluten CD4 + T cell response is strictly dependent on the antigen dose and not on the DQ2.5 gene configuration of APCs. Furthermore, our findings support the concept that the expression of DQ2.5 genes is an important risk factor in celiac disease. The preferential expression of DQ2.5 alleles provides a new functional explanation of why these genes are so frequently associated with celiac disease and with other autoimmune disorders. Highlights: The risk of celiac disease is related not only to HLA DQA1*05 and DQB1*02 (DQ2.5) genes but also to their expression. DQ2.5 homozygous and heterozygous antigen-presenting cells (APC) stimulate equally gluten-reactive CD4 + T cells. The strength of anti-gluten CD4 + T cell response is not strictly dependent on the HLA DQ2.5 gene dose of APC.